PS 09-23 PREVALENCE OF HYPERTENSION AND ASSOCIATED CARDIOVASCULAR RISK FACTORS IN A RURAL COMMUNITY OF EASTERN NEPAL. (September 2016) - Gautam, Rabin; Karki, Prahlad; Khanal, Vijay; Baral, Dharanidhar; Pokharel, Paras
Abstract : Objective: To find out the prevalence of hypertension along with other associated cardiovascular risk factors among adults in a rural community of Eastern Nepal. Design and Method: A community based cross sectional study was conducted in two of the randomly selected wards in Duhabi Village Development Committee, Sunsari, Nepal from September 2014-February 2015. A total of 624 participants above 40 years of age were interviewed by doing house to house survey. The data were collected using the WHO STEPS questionnaire. Hypertension was defined as systolic blood pressure (BP) = 140 and/or diastolic BP=90YmmHg or on treatment with BP lowering medications. Chi-square test and binary logistic regression analysis were used to show association between hypertension and selected variables. Results: The mean age (SD) of the participants was 51.47 (10.57) years. Hypertension was seen in 38.6% of participants. Obesity was seen in 11.2%, 41.5% were smokers, 20.2% consumed alcohol and 10.7% had elevated random blood glucose level (=200Ymg/dl). In binary logistic regression, age greater than 60 years (AORY=Y2.2, 95%CI; 1.37-3.67), stress (AORY=Y3.1, 95% CI; 1.80-5.36), alcohol consumption (AORY=Y1.60, 95%CI; 1.03-2.57), decreased physical activity (AORY=Y2.41; 95%CI; 1.66-3.49) and high waist circumference (AORY=Y1.73, 95%CIY=Y1.10-2.72) remained significantly associated with hypertension. Conclusions: The prevalence of hypertension in the rural community of Nepal was found to be high along with clustering of various risk factors. Thus effective intervention regarding prevention along with early diagnosis and treatment is necessary for control of increasing burden of hypertension in a rural setting.